ʻAnusō̜n nư̄ang nai ngān phrarātchathān phlœ̄ng sop Sāttrāčhān Phisēt Dō̜.Rō̜. Sunthō̜n Na Rangsī, Rātchabandit Mō̜.Pō̜.Chō̜., Mō̜.Wō̜.Mō̜. na mēn Wat Makutkasattriyārām Rātchawō̜rawihān, Khwǣng Bāng Khunphrōm, Khēt Phra Nakhō̜n, Krung Thēp Mahā NaKhō̜n, Wanʻāthit thī 3 Karakadākhom 2559. - Sunthorn Na-Rangsi, 1931-2016 (Krung Thēp : Khrō̜pkhrūa Na Rangsī, 2016)
Cremation volume for Sunthorn Na-Rangsi,1931-2016, a Thai philosopher, former professor of Faculty of Fine Arts, Chulalongkorn University and member of the Royal Institute; comprises biography and article on Buddhist philosophy.
Includes bibliographical references and index.
Keywords: Sunthorn Na-Rangsi, -- 1931-2016 -- Death and burial; Philosophers -- Thailand -- Biography; College teachers -- Thailand -- Biography; Buddhist philosophy